Household expenditure on non-Covid hospitalisation care during the Covid-19 pandemic and the role of financial protection policies in India - Samir Garg; Kirtti Kumar Bebarta; Narayan Tripathi (BMC, 2022)
Abstract Background Despite global guidance for maintaining essential non-Covid health services during the pandemic, there is a concern that existing services faced a major disruption. The access as well as affordability of healthcare could have suffered during the pandemic, especially in developing countries including India. There are no population based studies available in India on changes in access and financial risk for non-Covid hospitalisation during the pandemic. India has a policy of Publicly Funded Health Insurance (PFHI) to ensure access and financial protection for hospital care but no information is available on its performance during the pandemic. The current study was aimed to find out the change in access and financial protection for non-Covid hospitalisations during the Covid-19 pandemic and to examine the performance of PFHI in this context. Methods Panel data was analyzed, from two rounds of annual household surveys conducted in Chhattisgarh state for year 2019 and 2020. The survey followed a two-stage population based sample of around 3000 households, representative for the state. Two kinds of measures of catastrophic health expenditure were used - based on annual household consumption expenditure and on non-food consumption expenditure. Multivariate analysis was carried out to find determinants of utilisation and spending. In addition, Propensity Score Matching method was applied to find effect of PFHI schemes. Results Utilisation of hospital care per 1000 population reduced from 58.2 in 2019 to 36.6 during the pandemic i.e. in 2020. The share of public hospitals in utilisation increased from 60.1% in 2019 to 67.0% in 2020. Incidence of catastrophic expenditure was significantly greater during the pandemic. The median Out of Pocket Expenditure (OOPE) in private hospitals doubled from 2019 to 2020. The size of OOPE and occurrence of catastrophic expenditure were significantly associated with utilisation in private hospitals. Enrolment under PFHI schemes including the Ayushman Bharat-Pradhan Mantri Jan Arogaya Yojana (PMJAY) was not effective in reducing OOPE or catastrophic expenditure. Conclusion While the utilisation of hospital care dropped during the pandemic, the private hospitals became further unaffordable. The government policy for financial protection through health insurance remained ineffective during the pandemic.